Poty Women: organizational practices of the artisans of the Poty Velho Cooperative (Gestão & Regionalidade, 2024)
A community of practice is formed by a group of people with common goals, who together seek to improve in a given practice, aiming at professional differentiation. We selected as object of study women inserted in a low-income community who left a situation of co-adjuvancy for the protagonism, through handicrafts. Thus, the objective of this study is to understand how the organizational practices in the artisanal activity made possible the protagonism of the Poty Velho Women in Teresina-Piauí. The methodology adopted qualitative research with semi-structured interviews with three artisans, with the purpose of analyzing their organizational practices. Content analysis was used for data appreciation. The results demonstrate the evolution and recognition of artisans, taking into account the historical, material and human processes. It was concluded that the artisanal activity carried out by the women of Poty effectively constitutes a community of practice.
Keywords: Communities of Practice; Organizational practices; Women artisans